Dynamics of ion beam emission in a low pressure plasma focus device. (12th January 2021) - Lim, Lian-Kuang; Yap, Seong-Ling; Nee, Chen-Hon; Yap, Seong-Shan
Abstract: The plasma that accelerates and compresses in the formation of the pinch in dense plasma focus devices has been found to be an abundant source of multiple radiations like ion beams and x-rays. In this work, the ion beam and x-ray emissions from a 2.7 kJ (13.5 kV, 30 µ F) plasma focus device operated at pressure below 1 mbar were investigated. The time profile of the ion beam emission was analysed from the simultaneously measured ion beam, soft and hard x-ray signals using biased ion collectors, BPX 65 silicon PIN diode and a scintillator-photomultiplier tube assembly. Time resolved analysis of the emissions revealed that the emission of the ion beam corresponded to several different pinching instances. Two components of the ion beam were identified. An ion beam of lower energy but higher intensity was emitted followed by an ion beam of higher energy but lower intensity in the first plasma pinch. The ion beam emitted from the first plasma pinch also has higher energy than subsequent plasma pinches. The emission was found to be associated with the amplitude of voltage spike. The results from ion beam and electron beams suggest that they were emitted by the same localized electric field induced in the pinched plasma. The strongest plasma focus discharge indicated by sharp voltage spike of high amplitude and highest ion beam energy were both observed at 0.2 mbar. The average energy of the ion beam obtained is (53 ± 13) keV. At this optimum condition, the ions beam with the highest energy also led to the highest hard x-ray emission.